APP móvil para enseñanza aprendizaje de contenidos de CCNN en estudiantes de 9no básica de la Unidad Educativa Alfg. Vinafi - Orellana Capa, Klinton Alexander (Machala, Utmachala, 2022)
The purpose of this research work is the development of a mobile app that supports or facilitates the development of teaching strategies in students of the ninth year of General Basic Education, therefore, the use of technology for education is useful in strengthening the teaching-learning of the 21st century, where technology can break down the barrier of space and time of all students regardless of their culture, ethnicity, religion, among others. The research methodology was mixed research, which is the combination of quantitative and qualitative research, since it allows the collection, analysis and tabulation of information with open and closed questions, in order to obtain a greater amount of data from the respondents. Within the expected results, the mobile app LEARNCCNN was developed using Android Studio for its accessible programming environment, this mobile application was designed under the ADDIE model criteria, which according to Perez (2020) is an excellent model for the construction of prototypes due to its five phases; analysis, design, development, implementation and evaluation. Similarly, in experience 1 conducted at the school, data were obtained from the first survey for the improvement of the LEARNCCN mobile app so that in experience 2 the prototype can be easily used with the teacher's recommendations in the classroom. The LEARNCCNN mobile app obtained a favorable acceptance, as shown by the results obtained from the surveys applied to teachers and students, which show that the use of the mobile application dynamically increases the interest of students and strengthens the teaching-learning process.
El propósito de este trabajo de investigación es el desarrollo de una App Móvil que apoye o facilite el desarrollo de estrategias de enseñanza en los estudiantes del noveno año de Educación General Básica, por ende, la utilización de tecnología para la educación resulta ser útil en el fortalecimiento de la enseñanza-aprendizaje del siglo 21, donde la tecnología permita derribar la barrera de espacio y tiempo de todo el alumnado independientemente a su cultura, etnia, religión, entre otras. La metodología de investigación mixta, que es la combinación de lo cuantitativo y lo cualitativo, ya que esta permite la recopilación, análisis y tabulación de la información con preguntas abiertas y cerradas, con el fin de obtener una mayor cantidad de datos de los encuestados. Dentro de los resultados esperados se desarrolló la App Móvil LEARNCCNN donde se utilizó Android Studio por su entorno de programación accesible, esta aplicación móvil se diseñó bajo el criterio del modelo ADDIE, que de acuerdo con Pérez (2020) es un excelente modelo para la construcción de prototipos por sus cinco fases; análisis, diseño, desarrollo, implementación y evaluación. De igual forma en la experiencia 1 realizada en el plantel educativo se obtuvieron datos de la primera encuesta para la mejora de la App Móvil LEARNCCN con el fin que en la experiencia 2 el prototipo pueda ser usado con facilidad con las recomendaciones de la docente dentro de clases. La App Móvil LEARNCCNN obtuvo una favorable aceptación, tal como lo demuestran los resultados obtenidos de las encuestas que se aplicaron al docente y al alumnado, los cuales permiten apreciar que la utilización de la aplicación móvil aumenta de manera muy dinámica el interés de los alumnos y fortalece el proceso enseñanza aprendizaje.
Keywords: APP MOVIL; ESTRATEGIA METODOLOGICA; APRENDIZAJE MOVIL